2017
DOI: 10.1007/978-3-319-53412-1_19
|View full text |Cite
|
Sign up to set email alerts
|

How Does Interference Fall?

Abstract: We study how single-and double-slit interference patterns fall in the presence of gravity. First, we demonstrate that universality of free fall still holds in this case, i.e., interference patterns fall just like classical objects. Next, we explore lowest order relativistic effects in the Newtonian regime by employing a recent quantum formalism which treats mass as an operator. This leads to interactions between nondegenerate internal degrees of freedom (like spin in an external magnetic field) and external de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(68 reference statements)
3
2
0
Order By: Relevance
“…Version A is compatible with the results of Ref. [25], where it was shown that two-slit interference patterns fall like particles in a homogeneous gravitational field.…”
Section: Formulation Of the Equivalence Principlesupporting
confidence: 90%
See 1 more Smart Citation
“…Version A is compatible with the results of Ref. [25], where it was shown that two-slit interference patterns fall like particles in a homogeneous gravitational field.…”
Section: Formulation Of the Equivalence Principlesupporting
confidence: 90%
“…This statement of the EP also implies that wave function dispersion is the same for a free and a free-falling particle of the same type, which is a non-trivial prediction that is in principle testable. Version A is compatible with the results of [25], where it was shown that two-slit interference patterns fall like particles in a homogeneous gravitational field.…”
Section: Equivalence Principle For Quantum Systems Version Asupporting
confidence: 84%
“…The result also offers an interpretation of the Newtonian theory of particles with dynamical masses in terms of low-energy relativistic particles with dynamical internal degrees of freedom. Our results are relevant to the growing body of works studying relativistic effects in low-energy quantum systems [12][13][14][15][16][17][18][19], and clarify why MSR does not invalidate the analyses, contrary to some arguments [20].…”
supporting
confidence: 52%
“…Independently of its interpretation, the regime of lowenergy particles with dynamical mass-energy has its own symmetry and phenomenology, and can be studied fully in its own right. It has already allowed exploring proper time effects in unstable [9] and interfering quantum particles [12,[14][15][16]42], it was used to assess the limits to the notion of an ideal clock [19,43] and to the notion of time [30], and to study the role of mass-energy equivalence in atom-light interactions [17,44]. The approach has further enabled a quantum formulation of the EEP for composite particles [18] and can shed light on the role of proper time in quantum-to-classical transition [13,[45][46][47].…”
mentioning
confidence: 99%
“…We point out that [52][53][54][55] may be helpful for those interested in investigations similar in a sense to those dealt with in the present work.…”
Section: Final Remarksmentioning
confidence: 74%